Durability life prediction of RC piles subjected to localized corrosion in chloride environments. (June 2022) - Shao, Wei; He, Xiaoqing; Shi, Danda
Highlights: The durability life prediction model is proposed for localized corrosion in chloride environments. The localized corrosion process is divided into three stages, and an analytical approach is presented to predict the durability life. The effects of main influencing factors on the three stages of localized corrosion are investigated. Abstract: In this study, an analytical model for evaluating the durability life of reinforced concrete (RC) piles subjected to localized corrosion under chloride attack is proposed. The localized corrosion process is divided into three stages, and a predictive method is presented to predict the durability life of the pile by calculating the time of each stage. The time of each stage is determined based on the chloride diffusion model, the pitting corrosion model and the crack propagation model. The effects of the water-cement ratio, concrete cover thickness, pile concrete quality, relative humidity, chloride threshold level, pitting factor, corrosion current density and initial surface chloride ion concentration on the various stages of localized corrosion and the durability life of the pile are investigated. The analysis results show that the effects of the water-cement ratio and concrete cover thickness on the durability life of the pile are the most significant in the corrosion initiation stage. The durability life is increased by a reasonable choice of both concrete water-cement ratio and concrete cover thickness with constant concrete quality. The durability life of the pile increases with increasing concrete cover thickness, concrete quality, chloride threshold value and limit crack width, while it decreases with increasing water-cement ratio, relative humidity, corrosion current density and initial surface chloride concentration. The influence of the pitting factor is minimal and is mainly in the pit nucleation stage.